Text as Image in the Digital Age: A Formalist Reading of Polyvore Sets. - Bem, Caroline (Word & Image Interactions, 2015)
Polyvore.com is a platform where users are encouraged to mix and match images gleaned on the Internet. Even though Polyvore offers a standard writing tool as part of its interface, most occurrences of the written word in the collages stem from magazine pages, books, pièces of word art, or even digitized letters and manuscripts. Through a formalist reading of several Polyvore sets, I argue that the visual use of textual elements on Polyvore results from a heightened anxiety over the future of material objects of consumption, itself inextricably bound up with fears pertaining to the place of the printed word within the digital realm.